A study of cardiovascular sympathetic function tests during different phases of menstrual cycle in young females - Das, Shampa; Panja, Sumana; Samajdar, Kaushik (International Journal of Research in Medical Sciences, 2019)
Background: Menstrual cycle is a regular coordinated physiological change in non-pregnant women. The variation of hormonal concentrations during different phases of the menstrual cycle has a profound influence on autonomic and metabolic activities. The present study was designed to assess the cardiovascular sympathetic functions during different phases of menstrual cycle in normal healthy eumenorrheic females. Methods: Fifty females in the age group of 18-25 years were selected for the study. Non-invasive cardiovascular sympathetic function tests were performed during different phases of the menstrual cycle using RMS Polyrite D. Results: Results were analyzed using paired ‘t’ test. Resting blood pressure, blood pressure response to isometric handgrip test and cold pressor test were statistically significant higher (p-value <0.05), in the secretory phase as compared to menstrual and proliferative phase. Blood pressure response to orthostatic test was statistically significant between the proliferative and secretory phase and between menstrual and secretory phase (p-value <0.05). Conclusion: Our study shows that sympathetic activity is highest during the secretory phase of the menstrual cycle and lowest in the proliferative phase as compared to the menstrual phase. This higher sympathetic activity may be correlated with higher estrogen and progesterone levels during the secretory phase of the menstrual cycle. The study also emphasizes the complex relationship between ovarian hormones and autonomic regulatory systems.